Floating total knee: periprosthetic fracture of the distal femur combined with tibial plateau fracture in primary total knee arthroplasty - Modesto, Goncalo; Pires, João; Mendes, João; Seixas, João; Alegre, Carlos; Oliveira, João Pedro (International Journal of Research in Orthopaedics, 2024)
We are currently witnessing an increasing number of complications associated with arthroplasty, both due to its greater prevalence, whether primary or revision, and to the population’s longer average life expectancy. Periprosthetic fractures associated with a floating knee, in the context of total knee arthroplasty, are rare and their treatment is challenging. We present a case of ipsilateral periprosthetic fracture of the distal femur combined with fracture of the tibial plate in total knee arthroplasty. The 80-year-old female patient was admitted to the emergency department after falling from her own height at home. She reported diffuse pain in her right knee and associated functional incapacity. The limb was stabilized and immobilized in a posterior long leg splint. Initial X-rays showed an ipsilateral periprosthetic fracture of the distal femur and medial tibial plate. The patient’s only previous surgery was a total right knee arthroplasty performed in 2020. She underwent surgical treatment with osteosynthesis of the distal femur with a locked anatomical plate and arthroplasty revision of the tibial component. Periprosthetic fractures associated with knee arthroplasty typically involve the distal femur. Fractures involving the tibia are rare and usually occur in the medial tibial plate, in the presence of detachment of the tibial component. There is little published literature on this type of fracture in elderly patients. Periprosthetic fractures in total knee arthroplasty require individualized and planned treatment according to the personality of each fracture and the existence or not of prosthetic detachment.